1995
DOI: 10.1128/iai.63.4.1291-1297.1995
|View full text |Cite
|
Sign up to set email alerts
|

Human CAP18: a novel antimicrobial lipopolysaccharide-binding protein

Abstract: CAP18 (18-kDa cationic antimicrobial protein) is a protein originally identified and purified from rabbit leukocytes on the basis of its capacity to bind and inhibit various activities of lipopolysaccharide (LPS). Here we report the cloning of human CAP18 and characterize the anti-LPS activity of the C-terminal fragment. Oligonucleotide probes designed from the rabbit CAP18 cDNA were used to identify human CAP18 from a bone marrow cDNA library. The cDNA encodes a protein composed of a 30-amino-acid signal pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
252
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(264 citation statements)
references
References 59 publications
5
252
2
5
Order By: Relevance
“…Cationic AMP neutralize endotoxin's TLR4-dependent induction of cellular cytokine and nitric oxide release. This is accomplished either by binding directly to endotoxin or by blocking the binding of endotoxin to LBP thus attenuating or neutralizing endotoxin's inflammatory effects (Larrick et al, 1995;Scott et al, 2000;Nagaoka et al, 2001). Physico-chemical analysis of endotoxin indicates that lipid A conformation and supramolecular aggregate structure determine TLR4-dependent biological activity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic AMP neutralize endotoxin's TLR4-dependent induction of cellular cytokine and nitric oxide release. This is accomplished either by binding directly to endotoxin or by blocking the binding of endotoxin to LBP thus attenuating or neutralizing endotoxin's inflammatory effects (Larrick et al, 1995;Scott et al, 2000;Nagaoka et al, 2001). Physico-chemical analysis of endotoxin indicates that lipid A conformation and supramolecular aggregate structure determine TLR4-dependent biological activity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Beamer et al [46] concluded from LPS-binding studies of bactericidal permeabilityincreasing protein that two b-hairpin structures around residues 45 and 96 in the N-terminal domain KIKHLGK and KRFLK dominated by basic residues have been implicated in LPS binding. The C-terminal domain of human CAP18 contained a group of basic residues in the sequence KRIVQR (residues 123±128) and was observed to bind LPS [49,51]. Rustici et al [52] synthesized small peptide analogues of polymyxin B, a peptide-like antibiotic that binds LPS.…”
Section: Design Of Lipid a Pseudoreceptor Modelmentioning
confidence: 99%
“…36 The modulation of TLR function by cathelicidin can be considered an anti-inflammatory effect. 5 Cathelicidin downregulates signaling through TLR4, 37 whereas it stabilizes TLR3 ligands and enhances viral responses transmitted via this receptor in bronchial epithelial cells. 38 Although the cathelicidin molecule has a general anti-inflammatory effect on TLR stimulation by inhibiting the pro-inflammatory cytokine release from monocytic cells stimulated with TLR2 and TLR4, it can enhance or abrogate inflammatory signals depending on cell type and the microenvironment.…”
Section: Discussionmentioning
confidence: 99%